The Causal Factors Influencing of Purchase Decision Books on Thaibookfair Website in Bangkok and its Vicinity - Pankham, Sumaman; Plaiwech, Pornthep (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this article were 1) to develop and validate the consistency of purchase decisions for books on the Thaibookfair website in Bangkok and its vicinity and 2) to study causal factors influencing purchase decisions for books on the Thaibookfair website in Bangkok and its vicinity. This study was quantitative research. The sample consisted of people who have bought books on the Thaibookfair website and live in Bangkok and its vicinity of 400 people. The tools used in the research were online questionnaires. The statistics used in the data analysis were frequency, percentage, and structural equation models. The results of this research were the development of causal relationship models, consisting of five components: 1) brand image, 2) security, 3) perceived risk, 4) trust, and 5) purchase decision, and the model was consistent with the empirical data to a great extent. The statistics showed that the Chi-square statistics goodness fit test (2) = 321.63, degrees of freedom (df) = 233, CMIN/df = 1.38, GFI = 0.94, AGFI = 0.92, SRMR = 0.05, RMSEA = 0.03. The final predictive coefficient was 0.53, indicating that the model variables can explain 53% of the variance in book purchase decisions on the Thaibookfair Website. It was discovered that the one factor that had the greatest influence and direct effect on purchase decisions was trust. The results of this research, selling books business on the website should pay attention to the trust factor, to make buyers trust the quality of the books sold on the website.